Functional relevance of the lateral occipito-temporal cortex in body perception - Atilgan, Hicret (Nanyang Technological University, 2023)
One scientific challenge is understanding how information is processed in the brain to enable meaningful perceptual experiences. David Marr proposed three influential distinct levels of analysis for information-processing systems: computation, the algorithm, and implementation (Marr, 1982), which remain fundamental principles of cognitive science. These levels roughly correspond to the questions of where/what (implementation), how (algorithmic), and why (computational) that are posed in order to comprehend the mechanism underlying the behavior. In particular, the two levels of implementation and algorithmic have been the main focus of cognitive science research (Craver, 2007). The implementation level, also known as the "hardware", addresses how the representation and algorithm are physically realized. Electrophysiological and neuroimaging studies have been elucidating the functional organizations of the human brain at this implementation level. The algorithmic level, similar to a computer program, is concerned with the processes and representations that produce behavior. This algorithmic level has presented itself as a hot topic of research in cognitive neuroscience. It provides the neural mechanisms underlying the interaction between sensory systems – how separately processed sensory information is merged to give rise to perception/behavior. Currently, it is still debatable to what extent the sensory cortices, such as the visual cortex, are engaged in this multisensory processing. This thesis examines the above debate on the role of the visual cortex in the convergence and interaction between tactile and visual information by focusing on the cortical area called the Extrastriate Body Area (EBA) in the lateral occipito-temporal cortex, which is critical for the visual perception of body parts (Downing et al., 2001). Recent findings from neuroimaging studies show that EBA might be a multisensory region, also involved in processing non-visual sensorimotor and haptic modalities (Astafiev et al., 2004; Kitada et al., 2009, 2014) and possibly a supramodal region evident by congenitally blind studies (e.g., Kitada et al., 2014). However, it is unclear if EBA is essential for the processing of non-visual body parts because neuroimaging studies do not necessarily provide causal evidence. One way to establish causal evidence for the functional relevance of EBA is to perturb the activity (e.g., virtual lesion) by brain stimulation techniques and examine the behavioral change after the stimulation. Previous EBA stimulation studies using online repetitive transcranial magnetic stimulation (rTMS) showed that EBA stimulation disturbed the visual perception of body parts (Pitcher et al., 2009; Urgesi et al., 2004). By contrast, brain-stimulation studies on the lateral occipito-temporal cortex showed inconsistent results on its functional relevance for non-visual object processing (e.g., Ricciardi et al., 2011; Kassuba et al., 2014). Therefore, it is still an open question as to whether EBA is an essential region for non-visual object processing. Two brain-stimulation (repetitive transcranial magnetic stimulation, rTMS) studies on EBA were conducted to test the hypothesis that it is functionally relevant for visual and haptic object recognition, specifically for body parts and tools. A unique comparison of the effects of EBA stimulation with offline (unilateral - Study 1) and offline & online (bilateral- Study 2) stimulation protocols to determine the role of EBA on visual and haptic object processing is presented in this thesis. To the best of my knowledge, the functional relevance of EBA for processing non-visual body information was shown for the first time. Notably, the present findings helped to extend the current theoretical knowledge of EBA's role in visual body processing by showing impairment of visual body processing with an offline rTMS (cTBS) protocol. More importantly, these findings provided novel causal evidence for visual tool processing and haptic body processing in EBA. They confirm that EBA is functionally relevant for processing non-visual body information; rTMS over EBA modulated the perception of body parts across both vision and haptics. Moreover, unilateral and bilateral stimulation over EBA caused different modulations between haptic and visual hand recognition. My findings indicate differences in the contributions of bilateral EBA to visual and haptic body recognition. Therefore, this work contributes to understanding how haptic and visual body information interacts in the brain and provides evidence supporting that the occipito-temporal cortex is the multisensory and possibly the supramodal cortex for processing specific attributes of objects (e.g., object category).